Picture Fuzzy Weighted Distance Measures and their Application to Investment Selection - Meiling Liu; Shouzhen Zeng; Tomas Baležentis; Dalia Streimikiene (Amfiteatru Economic)
The picture fuzzy set (PFS) is a powerful tool to collect and handle large amounts of uncertain assess information in a new light. In this study, we explore some distance measures for the PFSs and propose Picture fuzzy ordered weighted distance measure and Picture fuzzy hybrid weighted distance measure. Some of their properties are also mathematically explored. Moreover, we introduce a model for the aforesaid distance measures to solve multiple attribute group decision making (MAGDM) method in an updated way. And at the end of our paper a practical application of investment alternatives selection is provided to illustrate the validity and applicability of the presented work.